FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - GALATHIA GALATHIA; MOHAMMAD EDDY ROSYADI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The objective of this research is to analyze factors influencing firm value on non-financial companies listed in Indonesia Stock Exchange. Those factors are debt policy, dividend policy, intangible asset, asset turnover, current ratio, profitability and size. Population of this research is non-financial companies which are consistently listed in Indonesia Stock Exchange from 2015 to 2017. Samples are obtained through purposive sampling method, in which only 116 of listed non-financial companies in Indonesia Stock Exchange meet the sampling criteria, resulting 339 firm-year observations used in this research. Multiple regression and hypotheses testing are used as the data analysis method in this research. The result of this research shows that debt policy, intangible asset and profitability have influence on firm value, whereas dividend policy, current ratio, asset turnover and size do not have influence on firm value